The Postsynaptic Density: There Is More than Meets the Eye - Dosemeci, Ayse; Weinberg, Richard J.; Reese, Thomas S.; Tao-Cheng, Jung-Hwa (Frontiers in Synaptic Neuroscience, 2016)
The postsynaptic density (PSD), apparent in electron micrographs as a dense lamina just beneath the postsynaptic membrane, includes a deeper layer, the “pallium,” containing a scaffold of Shank and Homer proteins. Though poorly defined in traditionally prepared thin-section electron micrographs, the pallium becomes denser and more conspicuous during intense synaptic activity, due to the reversible addition of CaMKII and other proteins. In this Perspective we review the significance of CaMKII-mediated recruitment of proteins to the pallium with respect to both the trafficking of receptors and the remodeling of spine shape that follow synaptic stimulation. We suggest that the level and duration of CaMKII translocation and activation in the pallium will shape activity-induced changes in the spine.